PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS NEARPOD TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SD INPRES BELAKA KABUPATTEN GOWA - Arsyad, Dian Fauziah; Irfan, Muhammad; Sayidiman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine: (1) an overview of the use of Nearpod based interactive learning media in IPAS learning, (2) students’ IPAS learning outcomes before and after the use of Nearpod based interactive learning media, and (3) the effect of using Nearpod based interactive learning media on IPAS learning outcomes of fifth grade students. This research employed a quasi experimental method with a nonequivalent control graoup design. The population of this study consisted of all fifth grade students of SD Inpres Belaka, Gowa Regency. The research sample was class VA as the experimental class, with and class VB as the control class, with 32 students in each class. The sampling technique used was total sampling. Data were collected through observation sheets on the implementation of Nearpod based interactive learning media and learning outcomes tests in the form of multiple choice questions consisting of pretest and posttest. Data analysis technique included descriptive statistics and inferential statistics using the independent sample t-test. The results showed that the use of Nearpod based interactive learning media was implemented very well, the IPAS learning outcomes of students in the experimental class and the control class. Based on the findings, it can be concluded that the use of Nearpod based interactive learning media has a significant effect on the IPAS learning outcomes of fifth grade students at SD Inpres Belaka, Gowa Regency.